2001
DOI: 10.1080/00288306.2001.9514951
|View full text |Cite
|
Sign up to set email alerts
|

Geology of the Permian Kuriwao Group, Murihiku Terrane, Southland, New Zealand

Abstract: Kuriwao Group rocks form a small inlier (5x2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It has been suggested that Wooded Peak Limestone and Tramway Formation are entirely Late Permian (Wuchiapingian-Changhsingian; see Waterhouse 1998Waterhouse ,2001Campbell 2000;Campbell et al 2001). If this is confirmed, then the West Dome occurrences significantly extend the known age ranges of Shulgapora, Dyscritellina, and Maychella.…”
Section: Bryozoamentioning
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that Wooded Peak Limestone and Tramway Formation are entirely Late Permian (Wuchiapingian-Changhsingian; see Waterhouse 1998Waterhouse ,2001Campbell 2000;Campbell et al 2001). If this is confirmed, then the West Dome occurrences significantly extend the known age ranges of Shulgapora, Dyscritellina, and Maychella.…”
Section: Bryozoamentioning
confidence: 84%
“…A more precise age assignment should be possible using the existing New Zealand Permian brachiopod zonal scheme developed by Waterhouse (1982Waterhouse ( , 1998Waterhouse ( ,2001. Palynological investigations may also prove fruitful (see Raine in Campbell et al 2001) but recrystallisation of the Maitai sequence at West Dome appears to be unfavourable and preliminary attempts have failed to produce identifiable palynomorphs. Other potential dating methods involve studies of stable isotopes and ion-microprobe analyses of clastic zircons.…”
Section: Age Of Maitai Group Strata At West Domementioning
confidence: 99%
“…The Murihiku Supergroup (or terrane) in the western North Island comprises five groups of rocks and ranges in age from Late Triassic (Oretian Stage) to at least (Campbell et al 2001). Only 10 of these stages, from Late Triassic to Late Jurassic, are present in the North Island (Kear 1964) (Fig.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The Murihiku Supergroup was initially defined by Campbell & Coombs (1966), and has been recently amended by Campbell et al (2003) to include Late Permian carbonate sequences in the Kuriwao Group in eastern Southland (Campbell et al 2001). The Murihiku Supergroup (or terrane) in the western North Island comprises five groups of rocks and ranges in age from Late Triassic (Oretian Stage) to at least (Campbell et al 2001).…”
Section: Geologic Settingmentioning
confidence: 99%
“…3; e.g., at Kawhia coast, Fleming & Kear 1960, fig. 3 Fleming & Kear (1960), Purser (1961), Campbell & Coombs (1966), Kear (1966), Skinner (1972Skinner ( , 1993, Waterhouse (1978), Ballance & Campbell (1993), Mortimer (1995a), Mortimer et al (1999), Campbell et al (2001), andCampbell et al (2003). Timescale of Gradstein et al (1995).…”
Section: Nature Of Kirikiri-apotu Contactmentioning
confidence: 99%